2014
DOI: 10.1007/s00467-014-2846-z
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate homeostasis in Bartter syndrome: a case–control study

Abstract: The results of this study demonstrate a tendency towards renal phosphate wasting and elevated circulating PTH levels in Bartter patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…(61) In addition, Bartter syndrome type 1 (neonatal), which is characterized by metabolic alkalosis, renal hypokalemia, and secondary hyperaldosteronism, (62) and is due to mutations in the sodium-potassium-chloride co-transporter-2 gene (SLC12A1), has also been reported to be associated with hypercalcemia, hypercalciuria, and nephrocalcinosis. (62)(63)(64) However, the hypercalcemia was associated with increased circulating PTH concentrations, which may be explained by an inappropriate response to hypocalcemia secondary to hypercalciuria (63) and is consistent with marginally increased circulating PTH concentrations that have been reported in other, older children with Bartter syndrome. (64)…”
Section: Renal Tubular Disorderssupporting
confidence: 79%
See 1 more Smart Citation
“…(61) In addition, Bartter syndrome type 1 (neonatal), which is characterized by metabolic alkalosis, renal hypokalemia, and secondary hyperaldosteronism, (62) and is due to mutations in the sodium-potassium-chloride co-transporter-2 gene (SLC12A1), has also been reported to be associated with hypercalcemia, hypercalciuria, and nephrocalcinosis. (62)(63)(64) However, the hypercalcemia was associated with increased circulating PTH concentrations, which may be explained by an inappropriate response to hypocalcemia secondary to hypercalciuria (63) and is consistent with marginally increased circulating PTH concentrations that have been reported in other, older children with Bartter syndrome. (64)…”
Section: Renal Tubular Disorderssupporting
confidence: 79%
“…(62)(63)(64) However, the hypercalcemia was associated with increased circulating PTH concentrations, which may be explained by an inappropriate response to hypocalcemia secondary to hypercalciuria (63) and is consistent with marginally increased circulating PTH concentrations that have been reported in other, older children with Bartter syndrome. (64)…”
Section: Renal Tubular Disorderssupporting
confidence: 79%
“…-Further studies are necessary to understand the pathophysiology of these abnormalities and to demonstrate whether PTH and/or phosphate should be a treatment target in these salt- In recent years, several investigators have observed abnormal levels of parathyroid hormone (PTH) and serum phosphate in patients with Bartter and Gitelman syndrome [3][4][5][6][7][8][9][10][11][12][13] . Patients with Bartter syndrome tend to have a high PTH [3][4][5][6][7][8][9] . However, the prevalence and pathophysiology of hyperparathyroidism in these Bartter patients are unclear.…”
Section: What Impact This May Have On Practice or On Policy?mentioning
confidence: 99%
“…Bartter syndrome 3,5 . In patients with Gitelman syndrome, high PTH levels have only been described in patients that had parathyroid adenoma 14,15 , while hypophosphatemia has been reported in several small studies [10][11][12][13] and has been attributed to renal phosphate wasting 12,13 .…”
Section: What Impact This May Have On Practice or On Policy?mentioning
confidence: 99%
“…A recent case-control study by Bettinelli et al [4] examined phosphate homeostasis in Bartter syndrome. The authors noted that hypercalciuria and nephrocalcinosis were well described in patients with this rare disease, but characterization of phosphate and calciotropic hormones in this disorder was quite limited.…”
Section: Case Seriesmentioning
confidence: 98%